Comparison between conventional and structured magnetic resonance imaging reports in perianal fistula - Paula Carolinada Silveira Pozzi Barbosa; Denise Maria Rissato Camilo; Thiago Franchi Nunes; Carlos Henrique Marquesdos Santos; Diogo Iengo Nakamura (Journal of Coloproctology, 2020)
Rationale: Very often magnetic resonance imaging is used in the study of complex anal fistulae, but conventional reports may contribute little to what really matters to the coloproctologist. Objective: To compare the clarity and usefulness of the conventional report compared to structured magnetic resonance imaging in cases of anal fistula. Method: 30 magnetic resonance exams already performed with an evaluation of anal fistula were again evaluated without the radiologist having access to the old report and a new structured report was prepared. Five proctologists evaluated the 30 conventional and 30 structured reports and answered questionnaires with eight questions comparing their practical aspects. The results were tabulated and submitted to statistical treatment considering a significant p < 0.05. Results: There was a statistically significant difference in favor of the structured report in the questions “clearly defines whether it is an active fistula or fibrosis”, “clearly states whether the tract is single or multiple”, “whether the patient has anal fistula or not”. The other questions did not present differences between the groups. Conclusion: The structured magnetic resonance report presented clearer information and was better evaluated in relation to the conventional one in the analysis of proctologists in the study of anal fistulae. Resumo: Racional: Com muita frequência utiliza-se ressonância magnética no estudo de fístulas anais complexas, porém, laudos convencionais podem contribuir pouco para o que realmente importa ao coloproctologista. Objetivo: Comparar a clareza e utilidade do laudo convencional com uma proposta de laudo estruturado de ressonância magnética em casos de fístula anal. Método: 30 exames de ressonância magnética já com laudo realizados para avaliação de fístula anal foram novamente avaliados sem que o radiologista tivesse acesso ao laudo antigo e foi confeccionado novo laudo estruturado. Cinco médicos proctologistas avaliaram os 30 laudos convencionais e os 30 estruturados e responderam a questionários com oito questões comparando aspectos práticos dos mesmos. Os resultados foram tabulados e submetidos a tratamento estatístico considerando-se significante p < 0,05. Resultados: Houve diferença estatisticamente significante em favor do laudo estruturado nos quesitos “define claramente se é fistula ativa ou fibrose”, “declara claramente se o trajeto é único ou múltiplo”, “fica clara a informação se o paciente tem ou não fistula anal”. Os demais quesitos não apresentram diferença entre os grupos. Conclusão: O laudo estruturado de ressonância magnética apresentou informações mais claras e foi melhor avaliado em relação ao convencional na análise dos proctologistas no estudo de fístulas anais. Keywords: Rectal fistula, Magnetic resonance imaging, Diagnosis, Radiology, Therapeutics, Palavras-chave: Fístula retal, Imagem por ressonância magnética, Diagnóstico, Radiologia, Terapêutica